A festa como transgressão das torcidas organizadas: uma etnografia da Torcida Tricolor Independente - Capestrani, Carlos Eduardo (2009)
Objective: This text intends to analyze the behavior of the soccer fan clubs parties that express the passion, joy and the aggressiveness of the soccer fan. Methods: A participant observation of the Torcida Tricolor Independente has been done in 2005 and 2006 in order to understand the group s actions through the point of view of the soccer fan, escaping from the stereotype of delinquents created by the media. The selection of this period of time was due to being the first two years that followed the official return of the soccer fan clubs to the soccer stadiums after ten years of the prohibition of its activities, with the commitment of not acting with violence, but only to party. Conclusions: With this participant observation I perceived that the soccer fans were really only partying. They were celebrating the victory of their team, the aggression of the rival soccer fans, the confrontation with the police, in short everything was a reason to celebrate. When facing the results of the participant observation with the theoretical referential, I came to the conclusion that the soccer fans, when into groups, temporarily transgress the social rules, by using violence, soccer passion and indignation towards the daily life as reasons to party